Crystal structures from 1D to 3D: triggered by the different coordination morphologies of ligands in different reaction systems. Issue 31 (11th July 2016) - Wu, Yunlong; Yang, Guo-Ping; Liu, Jiao; Yan, Yangtian; Luan, Xinjun; Zhang, Wen-Yan; Wang, Yao-Yu
Abstract : Seven new metal–organic frameworks have been synthesized by using Zn(ii ), Cd(ii ), Pb(ii ) ions and H4 L. Structure studies reveal that the solvents system and radius of the metal ions play a decisive role on networks of the complexes and the luminescent properties were also explored. Abstract : In this report, seven new luminescent metal–organic frameworks (LMOFs), [Zn(L)0.5 (H2 O)2 ]·H2 O (1 ), [Zn(L)0.5 (DMF)] (2 ), [Zn3 (L)(μ3 -OH)2 (H2 O)4 ] (3 ), [Zn2 (L)(DMA)(H2 O)]·5(H2 O) (4 ), [Cd(L)]·2(H3 O)·(H2 O) (5 ), [Cd2 (L)(H2 O)3 ] (6 ), and [Pb(L)0.5 (H2 O)] (7 ) (H4 L = [1, 1′:4′, 1′′-terphenyl]-2′, 3, 3′′, 5′-tetracarboxylic acid; DMF = N, N -dimethylformamide; DMA = N, N -dimethylacetamide) have been solvothermally synthesized by using Zn(ii ), Cd(ii ), Pb(ii ) ions and H4 L in different solvent systems, all of which have been routinely characterized by elemental analysis, FT-IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). Single-crystal X-ray diffraction analyses show the different dimensionalities (1D, 2D or 3D) of complexes1–7 . Comparative structural studies of1–7 reveal that the L 4− ligands adopt different coordination morphologies:1 (η 1 μ1 χ 1 ), 2 (η 2 μ2 χ 2 ), 3 (η 2 μ2 χ 2 ), 4 (η 2 μ2 χ 2 ; η 1 μ1 χ 1 ), 5 (η 2 μ1 χ 2 ), 6 (η 2 μ2 χ 2 ; η 2 μ2 χ 3 ), and7 (η 2 μ2 χ 2 ; η 2 μ3 χ 4 ) with Zn(ii ) (74 pm), Cd(ii ) (97 pm) and Pb(ii ) (119 pm) in different solvent systems, which produce the complexes with different frameworks. Complex1 displays a 1D dimeric chain. Complexes2 and5 present a 2D layer structure with a uninodal 4-connected sql net with a symbol of (4 4 ·6 2 ). Complexes3, 6 and7 have a 3D dense packing structure based on infinite 1D rod-like secondary building units (SBUs). Complex3 is designated as a binodal (4, 6)-connected fry topological net with the point symbol (5 10 ·6 3 ·7 8 )(5 4 ·6 2 ). The whole network of6 can be simplified as a binodal (4, 8)-connected flu topological net with a point symbol of (4 12 ·6 12 ·8 4 )(4 6 )2 . Complex7 can be seen as a new binodal (5, 10)-connected topological net with the point symbol (4 10 )2 (4 28 ·6 16 ·8). Complex4 shows a 3D framework based on a binuclear [Zn2 (CO)3 O3 ] SBU, which can be viewed as a uninodal 4-connected sra topological net with the point symbol (4 2 ·6 3 ·8). Further, the solid-state luminescence properties of the complexes were measured and studied intensively at room temperature.